Collagen Extracted from Persian Gulf Squid Exhibits Anti-Cytotoxic Properties on Apple Pectic Treated Cells: Assessment in an In Vitro Bioassay Model - Ladan DELPHI; Houri SEPEHRI; Elahe MOTEVASELI; Mohammad Reza KHORRAMIZADEH (Tehran University of Medical Sciences, 2016)
Background: Collagen-based three-dimensional (3D) in vitro systems have been introduced to study the physiological states of cells. As a biomolecule, collagen is usually extracted from terrestrial animals whilst aquatic animals like squid contain large amounts of collagen. Methods: In order to make effective use of marine organisms, we selected Persian Gulf squid in 2015 to extract the required collagen. Then, a 3D culture system based on the extracted collagen was applied to investigate cellular mechanisms in a native microenvironment. The formed collagen gel was used to investigate the growth of MDA-MB-231 breast cancer cells as well as responses to pectic acid. Results: The results revealed that the extracted collagen contained α, ß and γ components with high water holding capacity. This collagen formed a gel-like structure, which could promote the proliferation of MDA-MB-231 breast cancer cells. The MDA-MB-231 cells' viability in presence of pectic acid, demonstrating the cells' behavior in a 3D culture system. Conclusion: It seems that the collagen extracted from squid skin has type I collagen properties. It might be used as a substrate in 3D cell culture systems.   Keywords: Cell culture, Collagen, Pectic acid, Squid, 3D culture system